“A verdade é que somos dois e somos um”: a memória e o duplo na escrita borgeana - ALMEIDA, Carolina Silva (2021)
The present study aims to investigate the double theme and its relation with memory as a motivation resource of this phenomenon. As proposed, we will analyze it through the writing of the essayist, critic, poet and prose writer Jorge Luis Borges, an important name of the Argentine and universal literature. Therefore, the elected stories to compose the corpus of the research are: “El Otro” and “Veinticinco de agosto, 1983”, in the works El Libro de Arena (1975/2009) and La memoria de Shakespeare (1983/1998), respectively. In this perspective, it interests us to analyze these narratives considering the double and what motivates its occurrence. Regarding the duplicated state driving forces, we chose the memory as a propagation resource and resorted to the identity and memory philosophy to understand the conformations that are part of the individual. Hence, we listed as main theoretical assumptions the following critics and theorists: Otto Rank (2013), Nicole Fernandez Bravo (1998), Clément Rosset (1998), Paul Ricoeur (2007) and (2014), Bella Jozef (2005) and James Woodall (1999). As such, the course laid out further intends to connect memory and the double in order to promote self-discovery. At last, we came to the conclusion that the human condition goes beyond the duplicity state. It is, in fact, multiple.